Iowa Birdline update, December 14, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for December 14, 1992. The highlights for the update include sightings of a Black-legged Kittiwake, a first year Glaucous Gull, and a Dickcissel frequenting a feeder at Cordova Park. Also included are handwritten notes with sightings of a Greater White-fronted Goose, Thayer's Gull and a Long-eared Owl. Epson - sheet feed/flatbed